Manihot esculenta Crantz TMe-4011 - GLIS of the ITPGRFA (International Institute of Tropical Agriculture, 2019)
Plant Genetic Resource.
Taxonomy: Manihot esculenta Crantz
Common name(s): Cassava
Other names: 03/0177
Conserved by: International Institute of Tropical Agriculture (IITA), Nigeria
Local sample unique identifier: TMe-4011
Method of creation: Acquisition
Date: 2018-01-31
Historical: No
Biological status: Breeding/research material
MLS status: Included
Keywords: Plant Genetic Resource for Food and Agriculture; FOS: Biological sciences; FOS: Agriculture, forestry, and fisheries